ECONOMIC JUSTIFICATION OF HONEY PRODUCTION IN SERBIA - Nedić, Nebojša; Nikolić, Marija M; Hopić, Senad E (Journal of Agricultural Sciences (Belgrade), 2019)
Although beekeeping in Serbia has a long tradition, the interest of farmers for this branch of agricultural production depends on the expected economic benefits. Assessing the economic justification of beekeeping is based on the analysis of the revenues from honey production, as the main and often the only beekeeping product, and the expenses generated in production. The aim of the paper is to compare revenues and expenses in the production of honey and to determine the threshold of profitability. Calculation of the revenues and the expenses was made on the basis of data obtained in the survey of beekeepers and from the available secondary sources. The analysis showed that the profitability threshold is achieved with 68 colonies, or with production volume of 1,450 kg of honey. The values of the indicators of economic efficiency, productivity and profitability indicate that beekeeping is economically justified on farms with 100 and 200 colonies.